Editorial: Epistemic Justice in Performing Arts (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This editorial presents the proposal that vectorized the conception of this Thematic Dossier, which sought contributions that problematize and reflect on the current and historical context of Epistemic Justice in Performing Arts, covering the production and diffusion of knowledge in the field both in creative and academic contexts. Keeping in view the perspectives of anticolonialities, this dossier considered texts that address topics of Epistemic Justice in the Performing Arts in all its amplitudes and implications.
Keywords: epistemic justice; performing arts; aesthetics; anticolonialities